FORMULASI DAN UJI AKTIVITAS ANTI BAKTERI SEDIAAN SALEP EKSTRAK ETANOL DAUN SIRIH CINA (peperomia pellucida) TERHADAP BAKTERI Staphylococcus Aureus - Rika Puspita Sari (Jurnal Penelitian Farmasi & Herbal, 2022)
Chinese betel leaf (Peperomiapellucida) is one among the wild herbaceous plants belonging to the Piperaceae family which is employed as a natural medicine. The study's goal was to determine the antibacterial activity of an ethanol extract of Chinese betel leaf ointment against Staphylococcus aureus, as well as the optimal concentration. The test of the study was administered by the diffusion method using disc paper. The results of the characterization examination of Chinese betel leaf simplicia powder obtained water soluble extract content of 64.58%, ethanol soluble extract content of 24.95%, total ash content of three 3.2%, 5.9 % water of content and 0.28% acid insoluble ash content of and Simplisia contains alkaloids, flavonoids, tannins, and saponins. Staphylococcus aureus obtained a degree of 8% with a diameter of 16.81, the diameter of the inhibition zone of the Chinese betel leaf ethanol extract against. The ethanol extract of Chinese betel leaf exhibits antibacterial action against Staphylococcus aureus, according to the findings of the study. Keywords: Antibacterial activity, Chinese betel leaf Staphylococcus aureus